Higher Blood Cadmium Concentration Is Associated With Increased Likelihood of Abdominal Aortic Calcification - Qin, Zheng; Liu, Qiang; Jiao, Pengcheng; Geng, Jiwen; Liao, Ruoxi; Su, Baihai (Frontiers in Cardiovascular Medicine, 2022)
Aims: This study aimed to evaluate the association between blood cadmium concentration (BCC) and abdominal aortic calcification (AAC) in US adults aged ≥40 years. Methods: Data were obtained from the 2013-2014 National Health and Nutrition Examination Survey (NHANES). Participants without data about BCC and AAC scores were excluded. BCC was directly measured using inductively coupled plasma–mass spectrometry. AAC scores were quantified by the Kauppila scoring system, and severe AAC was defined as an AAC score >6. Weighted multivariable regression analysis and subgroup analysis were conducted to explore the independent relationship between cadmium exposure with AAC scores and severe AAC. Results: A total of 1530 participants were included with an average BCC of 0.47 ± 0.02 μg/L and AAC score of 1.40 ± 0.10 (mean ± standard error). The prevalence of severe AAC was 7.96% in the whole subjects and increased with the higher BCC tertiles (Tertile 1: 4.74%, Tertile 2: 9.83%, Tertile 3: 10.17%, P=0.0395). We observed a significant positive association between BCC with the AAC score (β=0.16, 95% CI: 0.01~0.30) and an increased risk of severe AAC (OR=1.45; 95% CI: 1.03~2.04). Subgroup analysis and interaction tests indicated that there was no dependence for the association of BCC and AAC. Conclusion: BCC was associated with a higher AAC score and an increased likelihood of severe AAC in US adults. Cadmium exposure is a risk factor for AAC, and attention should be given to the management of blood cadmium.